Tourism in the Polar Regions: The Sustainability Challenge - United Nations Environment Programme; The International Ecotourism Society (2016)
Tourism is a growing activity in the Polar Regions. In the Arctic, tourism is already an important component of the economies of the north. In the Antarctic, the number of tourists landing on continental Antarctica continues to rise sharply. There are serious concerns that tourism is promoting environmental degradation in the Polar Regions (especially in the Arctic) by putting extra pressures on land, wildlife, water and other basic necessities, and on transportation facilities. This publication explains issues and impacts of relevance to polar tourism and provides a selection of good practices for various stakeholders. The publication builds on UNEP-UNWTO 12 principles on sustainable tourism development. The trends and patterns of tourism in Polar Regions are summarised and agenda of policy implication is identified. The publication addresses the main challenges related with the following impacts of tourism in the Polar Regions: Land management Biodiversity conservation Cultural Heritage and Climate change.